A novel explanation of corneal clouding in a bone marrow transplant-treated patient with Hurler syndrome. (July 2016) - Yuan, Ching; Bothun, Erick D.; Hardten, David R.; Tolar, Jakub; McLoon, Linda K.
Abstract: One common complication of mucopolysaccharidosis I-Hurler (MPS1-H) is corneal clouding, which occurs despite current treatments, including bone marrow transplantation. Human corneas were obtained from a 14 year old subject with MPS1-H and visual disability from progressive corneal clouding despite a prior bone marrow transplant at age 2. This was compared to a cornea from a 17 year old donated to our eye bank after his accidental death. The corneas were analyzed microscopically after staining with Alcian blue, antibodies to collagen I, IV, VI, and α-smooth muscle actin. Differences in levels of expression of the indicated molecules were assessed. Corneas from Hurler and control mice were examined similarly to determine potential mechanistic overlap. The MPS1-H subject cornea showed elevations in mucopolysaccharide deposition. The MPS1-H and Hurler mice corneas showed increased and disorganized expression of collagen I and IV relative to the control corneas. The MPS1-H corneas also showed increased and disordered expression of collagen VI. Positive expression of α-smooth muscle actin indicated myofibroblast conversion within the MPS1-H cornea in both the patient and mutant mouse material compared to normal human and control mouse cornea. Increased deposition of collagens and smooth muscle actin correlate with corneal clouding, providing a potential mechanism for corneal clouding despite bone marrow transplantation in MPS1-H patients. It might be possible to prevent or slow the onset of corneal clouding by treating the cornea with drugs known to prevent myofibroblast conversion. Highlights: Despite bone marrow transplantation, corneal clouding occurs in mucopolysaccharidoses-1 Hurler (MPS1-H) subjects. Collagens I, IV, and VI were upregulated in human Hurler corneas, in mice collagens I and IV were increased. Myofibroblast conversion occurred in human and mouse Hurler corneas and may play a role in development of corneal clouding.